Tuning carrier density and phase transitions in oxide semiconductors using focused ion beams - Mei, Hongyan; Koch, Alexander; Wan, Chenghao; Rensberg, Jura; Zhang, Zhen; Salman, Jad; Hafermann, Martin; Schaal, Maximilian; Xiao, Yuzhe; Wambold, Raymond; Ramanathan, Shriram; Ronning, Carsten; et al. (Nanophotonics, 2022)
We demonstrate spatial modification of the optical properties of thin-film metal oxides, zinc oxide (ZnO) and vanadium dioxide (VO2) as representatives, using a commercial focused ion beam (FIB) system. Using a Ga+ FIB and thermal annealing, we demonstrated variable doping of a wide-bandgap semiconductor, ZnO, achieving carrier concentrations from 1018 cm-3 to 1020 cm-3. Using the same FIB without subsequent thermal annealing, we defect-engineered a correlated semiconductor, VO2, locally modifying its insulator-to-metal transition (IMT) temperature by up to ∼25 °C. Such area-selective modification of metal oxides by direct writing using a FIB provides a simple, mask-less route to the fabrication of optical structures, especially when multiple or continuous levels of doping or defect density are required.
CRIS-Team Scopus Importer:2023-04-20
Keywords: defect engineering; doping; focused ion beam; mask-free lithography; vanadium dioxide (VO; zinc oxide (ZnO)